Implementation of Honest Character Values ​​in Online Thematic Learning in Elementary Schools: Implementasi Nilai Karakter Jujur Pada Pembelajaran Tematik Secara Daring di Sekolah Dasar - Sela, Dita Permai; Kurniawan, Machful Indra (Universitas Muhammadiyah Sidoarjo, 2021)
The research objective is to describe the strategy, implementation and results of implementing the value of honest character in online thematic learning. This research method uses the validity of triangulation data, namely students and parents. The results of this research found several things, namely finding strategies in instilling strengthening character education for students, advantages and disadvantages in instilling strengthening the value of honest character. In conclusion, to instill character education strengthening online, you can use a learning model strategy.